SCIENTIFIC AND METHODOLOGICAL SECURITY OF THE FUNCTIONING OF THE CENTER OF KAR'IERI AND BUSINESS FOR THE DEVELOPMENT OF YOUTH ENTERPRISE (Innovative professional education, 2023)
The article states the importance of the Career Center and business as an organization, as a friendly mind for the start-up development of small businesses on the way to a complex of services and resources. The scientific and methodological support for the development of the Center for Career and Business is considered as a foundation for professional (professional and technical) education, which ensures the integration of the processes of education, science and business. The activity of the Center for Career and Business is established by relevant key bodies, regulated by a number of regulatory documents, which require selection of participants in the Center for Career and Business, the creation and development of small and medium-sized businesses.
Keywords: Career and business center, professional (professional and technical) education, youth education, entrepreneurial competence, career consulting